PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KOPERASI UNIT DESA PAKIS KABUPATEN MALANG - Bagas Baskoro; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to examine and analyze the effect of work motivation, work discipline and job satisfaction on the cooperative village unit of the fern, partially or jointly. The population and sample are all administrators, amounting to 35 people. Data collection through questionnaires and interviews. Data analysis in this study uses SPSS version 17. Sampling technique using questionnaire dissemination methods and data testing techniques used in this study include validity, reliability, normality, classic assumptions, multiple linear regression analysis, and research hypothesis testing . The analysis shows that the performance of employees in KUD Pakis is less than the maximum. resulting in inefficient work.Keywords: work motivation, work discipline and job satisfaction on employee performance